Module Development Based on Local Wisdom Using Contextual Teaching and Learning Models to Improve Learning Outcomes for Fourth Grade Elementary School Students - Zufaida Zufaida; Pargito Pargito; Nurlaksana Eko Rusminto (Budapest International Research and Critics University, 2023)
Education is an important factor in educating the nation's next generation who are expected to have broad intellectual insight, especially in studying local wisdom with contextual learning models. In this case, a teacher is required to be able to create a fun and meaningful learning atmosphere. Therefore, this paper aims to develop an appropriate, practical, effective, and efficient learning implementation plan that is oriented towards local wisdom in thematic subjects of grade IV SD. The development method used in this research is A Recursive Reflective Design and Development Model, better known by the acronym R2D2, and Research Development Research, better known as RDR. The R2D2 development model consists of three focuses, namely the focus of (a) Determination, (b) design and development, and (c) dissemination. The use of the three focuses was carried out with data collection techniques in the form of interviews and observations aimed at several schools at random. The results obtained are that the development of modules based on local wisdom has been tested by several experts and applied to research samples which show the results that the development of modules based on local wisdom in fourth grade elementary school subjects can be tested elsewhere.